(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The media has a lot of potential and has an impact on people’s lives on many different levels. Instead than involving discriminatory people, new media and its applications promote greater individual participation. While analysing the relationship between media and its audience, it is important to note that the media divides its audience according to their affiliations and areas of interest. The creation and acceptance of new media tools and applications make this point obvious. Individuals can subscribe to messages and information based on accessibility preferences and interest. It should be mentioned that using a media platform requires contact between users and a respect for one another’s cultures and values. The importance of language and attitude in comprehending the dynamic of accessibility is one of its most crucial components. In order to connect with people and pique their interest, language is crucial. The fact that language involves numerous political, social, and economic variables is one of the major issues in this regard. Identity of the people and other related qualities are defined by social, political, and cultural factors. Understanding the politics and dynamism of language in the communication process is of importance to the researcher, particularly with regard to language in new media applications. In this regard, by employing an interview schedule among social media users, the study tends to explore the dynamism of language and the attitude of the user in engaging with other audience through the media.